2007
DOI: 10.1007/s10955-007-9414-x
|View full text |Cite
|
Sign up to set email alerts
|

The Two Dimensional Kondo Model with Rashba Spin-Orbit Coupling

Abstract: We investigate the effect that Rashba spin-orbit coupling has on the low energy behaviour of a two dimensional magnetic impurity system. It is shown that the Kondo effect, the screening of the magnetic impurity at temperatures T < T_K, is robust against such spin-orbit coupling, despite the fact that the spin of the conduction electrons is no longer a conserved quantity. A proposal is made for how the spin-orbit coupling may change the value of the Kondo temperature T_K in such systems and the prospects of mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 28 publications
1
61
0
4
Order By: Relevance
“…In the absence of SO coupling, it is natural to adopt a basis of states having a definite z component of the orbital angular momentum about the impurity site. The transformation [14,28] …”
Section: B Mapping To a Two-channel Anderson Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of SO coupling, it is natural to adopt a basis of states having a definite z component of the orbital angular momentum about the impurity site. The transformation [14,28] …”
Section: B Mapping To a Two-channel Anderson Modelmentioning
confidence: 99%
“…(14) in an inequivalent manner; in particular, they have different Fermi wave vectors. It is also important to bear in mind that the index τ = ±1/2 (or ↑, ↓) labels the z component of the total angular momentum, although this reduces to the z component of spin for the impurity operators d τ .…”
Section: B Mapping To a Two-channel Anderson Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This direct reasoning is supported by basic arguments 3 stating that, due to time-reversal symmetry, spin-orbit scattering does not suppress the Kondo effect even though it breaks spin-rotation invariance. Subsequent investigations 4,5 confirmed this conclusion. At finite external magnetic field, time-reversal invariance is broken, and additional mechanisms affecting Kondo cotunneling arise together with the conventional Zeeman splitting of the impurity levels, as was demonstrated in Ref.…”
Section: Introductionmentioning
confidence: 66%
“…[16][17][18][19][20] As a different context, several theoretical studies have recently investigated the Kondo effect for a single impurity in two-dimensional electron gas with the Rashba spin-orbit (SO) coupling. [21][22][23][24][25][26] The Rashba coupling is one of the antisymmetric spin-orbit (ASO) interactions and has attracted much attention from numerous researchers of bulk systems, such as the spintronics in semiconductors, 27,28) topological insulators, 29,30) and non-centrosymmetric superconductors. 31) For the Rashba Kondo system, it has been found that the lowtemperature physics meets the Fermi liquid picture as described by the conventional Kondo model, although the Kondo temperature can be considerably increased in certain situations for a relatively strong coupling of the Rashba SO interaction.…”
Section: Introductionmentioning
confidence: 99%